2021
DOI: 10.2147/copd.s310630
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Medication Regimen Complexity with COPD Medication Adherence and Control

Abstract: Introduction Medication adherence is often low among people with chronic obstructive pulmonary disease (COPD) and medication regimen complexity may be a contributing factor. In this study, we sought to examine the role of medication regimen complexity in COPD medication adherence among patients with multimorbidity. Methods We performed cross-sectional analysis of data on COPD patients in primary care and pulmonary practices in New York City and Chicago (n=400). Regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…In our study, if the patient's enteral nutrition intake exceeded 50% within 6 weeks, nutritional therapy was considered ( 20 ). By comparing the value of the actual total doses taken divided by the total doses prescribed during the 6-week period, we determined whether the actual intake was more than 50% ( 21 ). The actual total doses taken were calculated by the actual purchase records from the outpatient.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, if the patient's enteral nutrition intake exceeded 50% within 6 weeks, nutritional therapy was considered ( 20 ). By comparing the value of the actual total doses taken divided by the total doses prescribed during the 6-week period, we determined whether the actual intake was more than 50% ( 21 ). The actual total doses taken were calculated by the actual purchase records from the outpatient.…”
Section: Methodsmentioning
confidence: 99%
“…Frequent treatment discontinuation suggests that a dose escalation strategy may not be useful in Asian patients. In contrast, Federman et al [35] observed a significant relationship between the number of medications taken, the incidence of dyspnea, and the severity of COPD. In contrast, Chan et al [36] found that COPD patients with low adherence overused inhaled corticosteroids (ICS) and underused long-acting bronchodilators.…”
Section: Medication Adherence In Copdmentioning
confidence: 88%
“…Yet, the most commonly utilized and validated objective scoring tool is the 65-item, weighted MRC Index (MRCI), which has been developed for outpatient use only [ 14 , 15 , 16 , 17 , 18 ]. The MRCI has been used to evaluate conditions such as neurological impairment in children and hypertension, diabetes, chronic obstructive pulmonary disease, and chronic kidney disease in adults [ 19 , 20 , 21 , 22 , 23 , 24 ]. The MRC for the intensive care unit (ICU) scoring tool has been developed and intended for use in critically ill patients [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRC scoring tools have the potential to aid in the identification of which patients may benefit from subsequent interventions (i.e., comprehensive medication review) [ 23 , 24 ]. In the critical care setting, the tool can further support the need for clinical pharmaceutical expertise and workload assignment to address the complex pharmacotherapeutic needs of the patient.…”
Section: Introductionmentioning
confidence: 99%